2021
DOI: 10.3389/fcimb.2021.755650
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Gut Bacteriophages in the Pathogenesis and Treatment of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, are chronic, relapsing intestinal inflammatory disorders. Although the molecular mechanisms governing the pathogenesis of IBD are not completely clear, the main factors are presumed to be a complex interaction between genetic predisposition, host immune response and environmental exposure, especially the intestinal microbiome. Currently, most studies have focused on the role of gut bacteria in the onset and development of IBD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 135 publications
0
14
0
Order By: Relevance
“…Similarly, as in the bacteriome, there are highly specific interindividual differences in phage communities. The limited understanding of phage biology and the microbiological aspect of disease means that additional in vivo and in vitro studies are required to elucidate the roles of gut phages in IBD development and treatment [ 31 ].…”
Section: The Role Of Gut Microbiota In Uc Pathogenesismentioning
confidence: 99%
“…Similarly, as in the bacteriome, there are highly specific interindividual differences in phage communities. The limited understanding of phage biology and the microbiological aspect of disease means that additional in vivo and in vitro studies are required to elucidate the roles of gut phages in IBD development and treatment [ 31 ].…”
Section: The Role Of Gut Microbiota In Uc Pathogenesismentioning
confidence: 99%
“…Bacteriophage richness was reported to be increased, whereas bacterial richness was reduced (129). Most studies have also showed elevated number but lower diversity of Caudovirales phages in UC and CD compared with healthy subjects (130).…”
Section: Phage Therapymentioning
confidence: 99%
“…In IBD, the phage composition -phageome-appears to be altered, but findings are inconsistent (129,130). Bacteriophage richness was reported to be increased, whereas bacterial richness was reduced (129).…”
Section: Phage Therapymentioning
confidence: 99%
“…Bacteriophages have been observed to induce phase variation in bacterial cells, leading to the switching 'OFF' of specific polysaccharides loci or increased expression of alternative polysaccharides with possible protective effects 30 . Moreover, they have been shown to be associated with intestinal inflammation and IBD in several studies 31,32 , including Nishiyama et al 33 who characterized temperate bacteriophages and their bacterial hosts in the IBDMDB metagenomics database. Here, using phage sequences from IBDMDB database, and compared the relative abundances of these phages between samples that displayed lower (<40%) or higher (>60%) ratios of the PSA promoter 'ON' orientation.…”
Section: Investigating Viral Associations To Orientation Of the Polys...mentioning
confidence: 99%